Compton scattering in noncommutative space-time at the Next Linear Collider - Mathews, P. (American Physical Soc, 2001)
We study Compton scattering in the noncommutative (NC) counterpart of QED. Interactions in NC QED have momentum dependent phase factors and the gauge fields have Yang-Mills type couplings; this modifies the cross sections and they are different from the commuting standard model. Collider signals of noncommutative space-time are studied at the Next Linear Collider (NLC) operating in the e gamma mode. Results for different polarized cases are presented and it is shown that the Compton process can probe the noncommutative scale in the range of 1-2.5 TeV for typical proposed NLC energies.